Endogenous Information and Privacy in Automobile Insurance Markets - Lilia Filipova (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
This paper examines the implications of insurers' offering a voluntary monitoring technology to insureds in automobile insurance markets with adverse selection and without commitment. Under the consideration of the inherent costs related to the loss of privacy, the paper analyzes the incentives of insureds to reveal information, whereby they can decide how much or what quality of information to reveal. It is also allowed for the possibility that high risk individuals might mimic low risk individuals. The resulting market equilibria are characterized and it is shown, that it might be optimal for insureds to reject the monitoring technology, but also that under certain conditions, which are specified in the paper, it might be optimal for insureds to reveal complete information. Concerning the welfare effects of introducing voluntary monitoring of insureds, if low risk individuals reject it, there will be no change to either risk type. If they accept it, this will make them better off and high risks may either be made better off or worse off depending on the initial equilibrium before a monitoring technology is offered. Unless it is optimal for individuals to reveal either zero or complete information, an all-or-nothing nature of the monitoring technology will not be efficient.
Keywords: D82; G22; 330; adverse selection; privacy; insurance; risk classification; endogenous information acquisition